Selective IL-13 inhibitors for the treatment of atopic dermatitis - Francisca Gonçalves; Egídio Freitas; Tiago Torres (Drugs in Context, 2021)
Background: Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases worldwide. AD pathogenesis is multifactorial, involving environmental and genetic factors. IL-13 stands out as one of the main cytokines in the pathophysiology of AD. Currently, dupilumab, which targets both IL-4 and IL-13 signalling, is the only biologic agent approved for the treatment of moderate-to-severe AD. New targeted biologic therapies are being developed, such as lebrikizumab and tralokinumab, two selective IL-13 inhibitors. This article reviews the role of IL-13 in AD and the most recent data on lebrikizumab and tralokinumab.